Hubungan Antara Self Confidence dan Kemampuan Pemecahan Masalah Matematika Siswa Kelas IV Sekolah Dasar - Rita Tri Rita Tri Ratnasari; Zikri Neni Iska; Anis Fuadah Z (Elementar : Jurnal Pendidikan Dasar, 2022)
This study aims to determine the relationship between self confidence and mathematical problem solving ability of fourth grade students at SDN. This study uses a quantitative method with a correlation design. This research was conducted at SDN with a sample of 35 students. Data collection was carried out using an instrument in the form of a self-confidence questionnaire with a Likert scale model and a mathematical problem-solving ability test in the form of an essay. The results of this study indicate that there is a positive and significant relationship between self-confidence and mathematical problem-solving abilities of fourth grade students at SDN with an r-count or Pearson correlation of 0.552> 0.334 with a significance value of 0.001 <0.05 which means that the higher the student's self-confidence value, the higher the mathematical problem solving ability of fourth graders at SDN, and vice versa. The value of the coefficient of determination of self confidence and mathematical problem solving ability is 30.47% and the remaining 69.53% is influenced by other factors